Unicompartmental Knee Arthroplasty Utilization among Early Career Surgeons: An Evaluation of the American Board of Orthopaedic Surgery Part-II Database - Carender, Christopher N.; Duchman, Kyle R.; Shamrock, Alan G.; Glass, Natalie A.; Brown, Timothy S. (The Journal of Knee Surgery, 2022)
An updated understanding of unicompartmental knee arthroplasty (UKA) utilization is needed. The purpose of this study was to evaluate temporal trends in volume and utilization of UKA among early-career surgeons and to examine the influence of fellowship training status on utilization of UKA. The American Board of Orthopaedic Surgery (ABOS) Part-II database was queried from 2010 to 2019 to identify candidates who reported ≥1 total knee arthroplasty (TKA) or UKA. Self-reported history of fellowship training experiences was recorded. “High-volume” surgeons were defined as performing ≥7 UKA over the ABOS Part-II collection period. Trends were evaluated with the Cochrane–Armitage test and generalized linear models. From 2010 to 2019, a total of 2,045 candidates (28.1%) reported ≥1 TKA, while 585 candidates (8.0%) reported ≥1 UKA. The number of candidates reporting ≥1 UKA significantly increased (p = 0.001). An increase in UKA volume was observed over the study period (p < 0.001). Rates of utilization of UKA relative to TKA did not change significantly over the study period (p = 0.11). Sixty-three (2.4%) candidates met the study definition for high-volume UKA utilization. UKA procedure volume increased among ABOS Part-II candidates over the study period; however, rates of UKA utilization relative to TKA volume remained unchanged. Increasing volume of UKA performed by early-career surgeons is likely secondary to an increased number of surgeons trained in adult reconstruction. Only 2.4% of candidates who reported performing at least one knee arthroplasty procedure met the threshold for a high-volume UKA practice. Early-career surgeons should remain conscientious of UKA volume in their practice.
Keywords: unicompartmental knee arthroplasty; total knee arthroplasty; volume; early career; ABOS